Language Learning Strategy and Its Impact on Students' Thinking Style at Senior High School - Arisman, Rizal; Nety, Nety; Rikardo, Rikardo (Pioneer: Journal of Language and Literature, 2022)
The objective of this study was to investigate the impact of strategy in studying language toward thinking style in EFL students senior high school students in the South Buton regency. A correlational design was used as the method of this research. There were 50 students from grade eleven involved in this research. The data collection used questionnaires as the instrument for both variables and analyzed using the regression test. This research found that the mean score for language learning strategies was 72.78, which was in the good category and the mean score for thinking style was 74.57, which was also in the good category. The hypothesis testing result indicated language learning strategies are significantly and strongly correlated to thinking style since the score of correlation was 0.775.